Measurement of b hadron lifetimes in pp collisions at $\sqrt{s} =$ 8 TeV - CMS collaboration (2255 authors); Nayak, Aruna; Bargassa, Pedrame; Beirão Da Cruz E Silva, Cristóvão; Di Francesco, Agostino; Faccioli, Pietro; Galinhas, Bruno; Gallinaro, Michele; Hollar, Jonathan; Leonardo, Nuno; Lloret Iglesias, Lara; Seixas, Joao; et al. (My University, 2018)
Measurements are presented of the lifetimes of the ${\mathrm {B}^0}$ , $\mathrm {B}^0_\mathrm {s}$ , $\mathrm {\Lambda }_\mathrm {b} ^0$ , and $\mathrm {B}_\mathrm {c}^+$ hadrons using the decay channels ${\mathrm {B}^0}\!\rightarrow \! \mathrm {J}/\psi \mathrm {K^{*}(892)}{}^{0}$ , ${\mathrm {B}^0}\!\rightarrow \! \mathrm {J}/\psi \mathrm {K^0_S}$ , $\mathrm {B}^0_\mathrm {s} \!\rightarrow \! \mathrm {J}/\psi \mathrm {\pi ^+}\mathrm {\pi ^-}$ , $\mathrm {B}^0_\mathrm {s} \!\rightarrow \! \mathrm {J}/\psi \mathrm {\phi (1020)}$ , $\varLambda _\mathrm {b}^0\!\rightarrow \!\mathrm {J}/\psi \mathrm {\Lambda }^{0}$ , and $\mathrm {B}_\mathrm {c}^+ \!\rightarrow \!\mathrm {J}/\psi \mathrm {\pi ^+}$ . The data sample, corresponding to an integrated luminosity of 19.7 $\,\text {fb}^\text {-1}$ , was collected by the CMS detector at the LHC in proton–proton collisions at $\sqrt{s}=8\,\text {Te}\text {V} $ . The ${\mathrm {B}^0}$ lifetime is measured to be $453.0 \pm 1.6\,\text {(stat)} \pm 1.8\,\text {(syst)} \,\upmu \text {m} $ in $\mathrm {J}/\psi \mathrm {K^{*}(892)}{}^{0}$ and $457.8 \pm 2.7\,\text {(stat)} \pm 2.8\,\text {(syst)} \,\upmu \text {m} $ in $ \mathrm {J}/\psi \mathrm {K^0_S}$ , which results in a combined measurement of $c\tau _{{\mathrm {B}^0}} = 454.1 \pm 1.4\,\text {(stat)} \pm 1.7\,\text {(syst)} \,\upmu \text {m} $ . The effective lifetime of the $\mathrm {B}^0_\mathrm {s}$ meson is measured in two decay modes, with contributions from different amounts of the heavy and light eigenstates. This results in two different measured lifetimes: $c\tau _{\mathrm {B}^0_\mathrm {s} \rightarrow \mathrm {J}/\psi \mathrm {\pi ^+}\mathrm {\pi ^-}} = 502.7 \pm 10.2\,\text {(stat)} \pm 3.4\,\text {(syst)} \,\upmu \text {m} $ and $c\tau _{\mathrm {B}^0_\mathrm {s} \rightarrow \mathrm {J}/\psi \mathrm {\phi (1020)}} = 443.9 \pm 2.0\,\text {(stat)} \pm 1.5\,\text {(syst)} \,\upmu \text {m} $ . The $\mathrm {\Lambda }_\mathrm {b} ^0$ lifetime is found to be $442.9 \pm 8.2\,\text {(stat)} \pm 2.8\,\text {(syst)} \,\upmu \text {m} $ . The precision from each of these channels is as good as or better than previous measurements. The $\mathrm {B}_\mathrm {c}^+$ lifetime, measured with respect to the ${\mathrm {B}^{+}}$ to reduce the systematic uncertainty, is $162.3 \pm 7.8\,\text {(stat)} \pm 4.2\,\text {(syst)} \pm 0.1\,(\tau _{{\mathrm {B}^{+}}})\,\upmu \text {m} $ . All results are in agreement with current world-average values.